2013
DOI: 10.4236/ojas.2013.31005
|View full text |Cite
|
Sign up to set email alerts
|

Bovine <i>β</i>-casein: Detection of two single nucleotide polymorphisms by bidirectional allele specific polymerase chain reaction (BAS-PCR) and monitoring of their variation

Abstract: Due to the functional importance of bovine milk protein polymorphisms, their correct discrimination is of great interest both from a scientific and practical point of view. Nowadays a large number of commercial platforms are available for semi-automated or fully automated SNP genotyping. However, in some cases the use of simple and rather cheap methods is an effective tool to be implemented within one's own laboratory for the routine analysis of a specific SNP. The present paper describes two simple tests base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
(30 reference statements)
3
11
2
1
Order By: Relevance
“…Here, the B allele (frequency, 0.16) was overrepresented compared with the A 1 allele (0.07) in the CSN2 rs43703011 allele C genes. This finding is similar to that from a previous report on the Brown Swiss (Chessa et al, 2013). At present, it is not possible to establish whether the less favorable effect of the CSN2 rs43703011 A variant on RCT is due to the presence of the A 1 or B alleles, and the positive effect of the CSN2 B allele reported by Bittante et al (2012) remains controversial.…”
Section: Association Analysis With Traditional Mcpssupporting
confidence: 73%
See 2 more Smart Citations
“…Here, the B allele (frequency, 0.16) was overrepresented compared with the A 1 allele (0.07) in the CSN2 rs43703011 allele C genes. This finding is similar to that from a previous report on the Brown Swiss (Chessa et al, 2013). At present, it is not possible to establish whether the less favorable effect of the CSN2 rs43703011 A variant on RCT is due to the presence of the A 1 or B alleles, and the positive effect of the CSN2 B allele reported by Bittante et al (2012) remains controversial.…”
Section: Association Analysis With Traditional Mcpssupporting
confidence: 73%
“…Thus, even if the other CSN3 loci failed during the analysis (possibly because these SNPs are too close together, compromising primer hybridization), the frequency of the B allele in our population could be estimated at about 0.78. This was even higher than that found by Chessa et al (2013), who reported it increasing from 0.64 to 0.71. This indicates that selection is rapidly increasing the frequency of the B allele.…”
Section: Association Analysis With Traditional Mcpscontrasting
confidence: 64%
See 1 more Smart Citation
“…In 2005, Dutch Holstein Friesian A 2 plus I accounted for 0.692, A 1 for 0.285, A 3 for 0.001, and B for 0.022, showing an increase in the frequency of β-CN A 2 at the expense of β-CN A 1 compared to a previous study carried out in 1989 [19]. Conversely, in Italian Friesian no substantial modification of the frequency of β-CN variants was found in a 10-year period [20]. In Swedish Holstein, the frequencies of β-CN A 2 , β-CN A 1 , and B were 0.60, 0.34, and 0.06, respectively [18].…”
Section: Content Of β-Cn In Bulk Milk Samplesmentioning
confidence: 60%
“…As an example, we refer to Holstein Friesian which is the most common dairy breed, spread all over the world for its high milk yield. In Italian Friesian, the frequency of β-CN A 2 plus I variants accounted for 0.570, followed by A 1 (0.395), and B (0.035) [20]. It is necessary to point out that A 2 and I variants comigrate in IEF, but these variants differ for one amino acid exchange (Met 93 in A 2 to Leu 93 in I) not affecting Pro 67 , which is carried by both polypeptides [21].…”
Section: Content Of β-Cn In Bulk Milk Samplesmentioning
confidence: 99%